The Effects of Input-Based Practice on Pragmatic Development of Requests in L2 Chinese - Li, Shuai (Language learning, 2012)
This study examined the effects of input‐based practice on developing accurate and speedy requests in second‐language Chinese. Thirty learners from intermediate‐level Chinese classes were assigned to an intensive training group (IT), a regular training group (RT), and a control group. The IT and the RT groups practiced using four Chinese request‐making forms via computerized structured input activities over 2 consecutive days. During this time, the IT group practiced using the request‐making forms twice as much as the RT group. The control group did not practice. The results show that the input‐based practice was effective in promoting accuracy in an Oral Discourse Completion Task and in enhancing speed in a Pragmatic Listening Judgment Task. No other effects of practice were observed.